Outcomes of Snakebite Envenomation in Children - Shrestha, BM (Journal of Nepal Paediatric Society, 2011)
Introduction: Snakebite is a medical emergency, and is considered to be one of the major public health hazards in the Terai and inner-Terai regions of Nepal. Very few studies have been conducted so far in Nepal to highlight the epidemiology of snakebite in children. Aim: To review the pattern and characteristics of snakebites in children, focusing primarily on the outcomes, fatality and risk factors for death. Settings: An emergency department of a 136-bedded secondary care-referral hospital (Lumbini Zonal Hospital) situated at Butwal in the Western Nepal. Methodology: The study was carried out in 152 children aged < 15 years old, who got anti-snake venom (ASV) over a period of 48 months. Diagnosis of snakebite envenomation was based on clinical ground. Results: Children over 5 years of age constituted the highest number (87%) of cases. Peak incidence of poisoning (71%) was observed during the months of Asadh- Bhadra (June-September). Most of the bites (61%) were by unidentified snakes, most commonly (91%) on the extremities. Snakebite envenomation occurred more frequently (52%) during night time. 85% of children had local or systemic complications, commonest being respiratory paralysis(92/152).Case fatality rate (CFR) was 28%. Risk factors for death were: age < 5 years; bites by unidentified snakes and kraits and bites on ears & unknown sites. Conclusion: Compared with adults, children with snake envenomation have higher morbidity and mortality, which can be minimized by early diagnosis, appropriate treatment and close monitoring of children on ventilation for the timely management of complications. Emphasis should be given on developing a standard management protocol in children. Keywords: Snakebite; Envenomation; Children; Outcomes; Nepal DOI: http://dx.doi.org/10.3126/jnps.v31i3.5358 J Nep Paedtr Soc 2011;31(3):192-197